FUNDING STRATEGIES: SURVIVING IMPERIAL INTENTIONS, PROTEAN POLICIES AND RUTHLESS REALITY - de V Smit, André (Social Work/Maatskaplike Werk, 2005)
William Bolitho [Twelve Against the Gods, ‘Lola Montez’] enchantingly stated that “You need more tact in the dangerous act of giving...than in any other social action.” The act of giving funds in the welfare world is hazardous and sadly, many of our welfare mandarins eschew tact – some even think ‘tact’ is an acronym for some technical application